Tingkat Suku Bunga, Kinerja Keuangan, dan Bagi Hasil Deposito Pada Perbankan Syariah - Yudhistira Ardana; W Wulandari (Faculty of Economic and Business, 2018)
The composition deposit fund in the last three years had increased in sharia banks mainly in the form of time deposits. This study aims to analyze the Interest Rate, Financial Performance and Profit Sharing on Islamic Banking. This research used error correction model as tools of analysis. The results showed that in the short term the variables that significantly influence the profit sharing of mudharabah deposits in the sharia banks in Indonesia are BOPO and ROA, while the FDR, NPF and BI rate variables have no effect. In the long term the influential variables are BOPO, FDR, NPF and BI rate, while ROA has no effect. This result implies that profit sharing yields determined by some of the financial performance indicators, and not affected by the interest rate.DOI: 10.15408/ess.v8i2.8392